Anti-bacterial Treatment of Polyethylene by Cold Plasma for Medical Purposes - Popelka, Anton (Molecules, 2012)
Polyethylene (PE) is one of the most widely used polymers in many industrial applications. Biomedical uses seem to be attractive, with increasing interest. However, PE it prone to infections and its additional surface treatment is indispensable. An increase in resistance to infections can be achieved by treating PE surfaces with substances containing antibacterial groups such as triclosan (5-Chloro-2-(2,4-dichlorophenoxy)phenol) and chlorhexidine (1,1'-Hexamethylenebis[5-(4-chlorophenyl)biguanide]). This work has examined the impact of selected antibacterial substances immobilized on low-density polyethylene (LDPE) via polyacrylic acid (PAA) grafted on LDPE by low-temperature barrier discharge plasma. This LDPE surface treatment led to inhibition of Escherichia coli and Staphylococcus aureus adhesion; the first causes intestinal disease, peritonitis, mastitis, pneumonia, septicemia, the latter is the reason for wound and urinary tract infections.